A cobalt-free positive electrode material and a preparation method and application thereof

CN117317214BActive Publication Date: 2026-10-30TIANJIN B&M SCI & TECH LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311254784.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2026-10-30
Estimated Expiration
2043-09-26

AI Technical Summary

Technical Problem

然而,镍酸锂正极材料也存在一些问题,制约了其应用:充电态下Ni4+的高氧化性造成材料表面和电解液易发生副反应,造成性能衰退;正极材料对水敏感,材料制备和电池制作工艺要求高;多晶颗粒存在晶间应力,容易产生裂纹,降低材料的稳定性等

Benefits of technology

[0031](1)本发明的无钴正极材料,通过高价态Nb(铌)元素和Sb(锑)元素的协同作用,可在无钴正极材料的表面诱导形成纳米级阳离子混合相层,进而可提高正极材料中H2-H3相变可逆性,使其兼顾高容量和结构稳定性;同时,过渡元素Nb在正极材料的表面形成Nb-O离子键,进而可有效抑制表面氧的活性,提高材料结构稳定性,抑制电解液对材料的腐蚀,进而减少金属离子的溶出。本发明的无钴正极材料的结构稳定好,电化学性能好。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117317214B_ABST
    Figure CN117317214B_ABST
Patent Text Reader

Abstract

The present application relates to the field of battery, and particularly relates to a cobalt-free positive electrode material and a preparation method and application thereof. x Ni 1‑q‑m Nb q Sb m O2, wherein, 1.03<=x<=1.05, 0.001<=q<=0.003, 0.001<=m<=0.003. The cobalt-free positive electrode material of the present application can fix surface oxygen, reduce metal dissolution and improve phase transition reversibility of the positive electrode material through the synergistic effect of niobium and antimony.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of batteries, and more specifically, to a cobalt-free cathode material, its preparation method, and its application. Background Technology

[0002] Lithium-ion batteries possess advantages such as high specific energy, high operating voltage, long cycle life, and environmental friendliness, and are widely used in everyday electronic products. With the rapid development of the global electric vehicle and renewable energy industries, the market demand for lithium-ion batteries is growing rapidly. As one of the cathode materials for lithium-ion batteries, lithium nickel oxide (LiNiO) has attracted widespread attention due to its advantages such as high capacity and low cost. However, LiNiO cathode materials also have some problems that restrict their application: NiO in the charging state... 4+ The high oxidizing properties of cathode materials make them prone to side reactions on the material surface and in the electrolyte, leading to performance degradation. Cathode materials are sensitive to water, requiring sophisticated material preparation and battery manufacturing processes. Polycrystalline particles exhibit intergranular stress, which easily causes cracks and reduces material stability. Existing technologies employ hydrothermal reactions, which are difficult to control under controlled conditions, or other complex preparation processes, causing significant damage to the material structure.

[0003] In view of this, the present invention is hereby proposed. Summary of the Invention

[0004] One objective of this invention is to provide a cobalt-free cathode material that, through the synergistic effect of niobium and antimony, can fix surface oxygen, reduce metal dissolution, and improve the phase transition reversibility of the cathode material.

[0005] Another objective of this invention is to provide a method for preparing the cobalt-free cathode material, which has a simple preparation process, short cycle, high production capacity, and is environmentally friendly.

[0006] Another object of the present invention is to provide a battery having excellent charge / discharge capacity and first-efficiency.

[0007] Another object of the present invention is to provide an electrical device.

[0008] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted:

[0009] A cobalt-free cathode material, wherein the chemical formula of the cobalt-free cathode material includes Li x Ni 1-q-m Nb q Sb m O2, where 1.03≤x≤1.05, 0.001≤q≤0.003, and 0.001≤m≤0.003.

[0010] In one embodiment, the surface of the cobalt-free cathode material has a nanoscale cation mixed phase layer; the surface of the cobalt-free cathode material has Nb-O ionic bonds.

[0011] In one embodiment, the thickness of the nanoscale cationic mixed phase layer is 5–10 nm.

[0012] In one embodiment, the full width at half maximum (FWHM) of the cobalt-free cathode material is 0.09° to 0.12°.

[0013] In one embodiment, the residual alkali content of the cobalt-free cathode material is less than 5000 ppm.

[0014] In one embodiment, the specific surface area of ​​the cobalt-free cathode material is 0.2–0.4 m². 2 / g.

[0015] In one embodiment, the tap density of the cobalt-free cathode material is 2.2–5 g / cm³. 3 .

[0016] A method for preparing a cobalt-free cathode material includes the following steps:

[0017] Nickel hydroxide, lithium source, niobium source and antimony source are mixed and then sintered in an oxygen-containing atmosphere.

[0018] In one embodiment, the lithium source includes at least one of lithium hydroxide and lithium carbonate.

[0019] In one embodiment, the niobium source includes at least one of Nb-containing oxoacid salts, hydroxides, and oxides.

[0020] In one embodiment, the antimony source includes at least one of an oxoacid salt, hydroxide, and oxide containing Sb.

[0021] In one embodiment, the molar ratio of the nickel hydroxide and the lithium source, based on the elements of nickel and lithium, is 1:(1.03 to 1.05); the mass of the niobium source is 0.1% to 0.3% of the mass of the nickel hydroxide; and the mass of the antimony source is 0.1% to 0.3% of the mass of the nickel hydroxide.

[0022] In one embodiment, the nickel hydroxide has a sulfur content ≤800 ppm, a particle size D50 of 10–12 μm, a δPSD of 1.15–1.25, and a specific surface area of ​​20–24 m². 2 / g; tap density is 1.8–2.5 g / cm³. 3 Magnetic foreign matter <30ppb; Moisture content of nickel hydroxide <3000ppm.

[0023] In one embodiment, the mixing speed is 900-1100 rpm, and the mixing time is 30-50 min.

[0024] In one embodiment, the sintering temperature is 600–800°C, and the sintering time is 10–16 h.

[0025] In one embodiment, the oxygen-containing atmosphere contains 98% to 99.5% oxygen by volume.

[0026] In one embodiment, the heating rate of the sintering process is 2 to 4 °C / min.

[0027] In one embodiment, after the sintering process, the material is cooled in the furnace, and then crushed and screened.

[0028] A battery comprising the cobalt-free cathode material or the cobalt-free cathode material prepared by the method for preparing the cobalt-free cathode material.

[0029] An electrical device, including the battery.

[0030] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0031] (1) The cobalt-free cathode material of the present invention, through the synergistic effect of high-valence Nb (niobium) and Sb (antimony) elements, can induce the formation of a nanoscale cation mixed phase layer on the surface of the cobalt-free cathode material, thereby improving the reversibility of the H2-H3 phase transition in the cathode material, thus achieving both high capacity and structural stability; at the same time, the transition element Nb forms Nb-O ionic bonds on the surface of the cathode material, thereby effectively suppressing the activity of surface oxygen, improving the structural stability of the material, suppressing the corrosion of the material by the electrolyte, and thus reducing the dissolution of metal ions. The cobalt-free cathode material of the present invention has good structural stability and good electrochemical performance.

[0032] (2) The method for preparing the cobalt-free cathode material is simple, has a short cycle, high production capacity and is environmentally friendly.

[0033] (3) The battery obtained by the present invention using the above-mentioned cathode material has superior electrochemical performance, high structural stability, and high safety performance. Attached Figure Description

[0034] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0035] Figure 1 This is a diagram showing the charge and discharge capacity of the battery corresponding to the cobalt-free cathode material in Embodiment 1 of the present invention.

[0036] Figure 2 This is the X-ray diffraction pattern of the cobalt-free cathode material of Embodiment 2 of the present invention;

[0037] Figure 3 This is a scanning electron microscope image of the cobalt-free cathode material of Example 3 of the present invention;

[0038] Figure 4 This is a scanning electron microscope image of the cathode material used in the comparative example of this invention. Detailed Implementation

[0039] The embodiments of the present invention will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer are followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0040] According to one aspect of the present invention, the present invention relates to a cobalt-free cathode material, the chemical formula of which includes Li x Ni 1-q-m Nb q Sb m O2, wherein 1.03≤x≤1.05, 0.001≤q≤0.003, 0.001≤m≤0.003. The surface of the cobalt-free cathode material has a nanoscale cation mixed phase layer; the surface of the cobalt-free cathode material has Nb-O ionic bonds.

[0041] During repeated charge-discharge processes, the H3 phase in high-nickel materials can exhibit high capacity transfer and high delithiation states. However, to maintain the stability of the layered structure under high delithiation states, the reversible appearance of the H3 phase during charging must be ensured. The cobalt-free cathode material of this invention, through the synergistic effect of high-valence Nb (niobium) and Sb (antimony) elements, can induce the formation of a nanoscale cation mixed phase layer on the surface of the cobalt-free cathode material, thereby improving the reversibility of the H2-H3 phase transition in the cathode material and achieving a balance between high capacity and structural stability. Simultaneously, the transition element Nb forms Nb-O ionic bonds on the surface of the cathode material, which can effectively suppress the activity of surface oxygen, improve the structural stability of the material, inhibit the corrosion of the material by the electrolyte, and reduce the dissolution of metal ions.

[0042] In one embodiment, the thickness of the nanoscale cationic mixed phase layer is 5 to 10 nm, for example, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm.

[0043] In one embodiment, the half-width at half maximum (FWHM) (003) of the cobalt-free cathode material is 0.09° to 0.12°, for example, 0.09°, 0.1°, 0.11°, 0.12°, etc.

[0044] In one embodiment, the residual alkali content of the cobalt-free cathode material is less than 5000 ppm, such as 1000 ppm, 2000 ppm, 3000 ppm, 4000 ppm, etc.

[0045] In one embodiment, the specific surface area of ​​the cobalt-free cathode material is 0.2–0.4 m². 2 / g, for example 0.2m 2 / g, 0.22m 2 / g, 0.25m 2 / g, 0.28m 2 / g, 0.3m 2 / g, 0.32m 2 / g, 0.35m 2 / g, 0.38m 2 / g, 0.4m 2 / g etc.

[0046] In one embodiment, the tap density of the cobalt-free cathode material is 2.2–3 g / cm³. 3 For example, 2.2g / cm 3 2.5g / cm 3 2.8g / cm 3 3g / cm 3 wait.

[0047] The cobalt-free cathode material of the present invention has a suitable specific surface area and tap density, thereby ensuring the excellent electrochemical performance of the cathode material.

[0048] According to another aspect of the present invention, the present invention also relates to a method for preparing a cobalt-free cathode material, comprising the following steps:

[0049] Nickel hydroxide, lithium source, niobium source and antimony source are mixed and then sintered in an oxygen-containing atmosphere.

[0050] This invention involves first dry mixing nickel hydroxide and a lithium source to ensure thorough homogenization, followed by the addition of niobium and antimony sources for further mixing. In one embodiment, the niobium and antimony sources are simultaneously added to the mixture of nickel hydroxide and lithium source for further mixing. In another embodiment, the niobium and antimony sources are added in batches for mixing. This invention requires only a single sintering process; after sintering, the material is further crushed and sieved to obtain cathode material of suitable particle size. The cobalt-free cathode material prepared by this invention has a simple preparation method, high production capacity, and is environmentally friendly.

[0051] In one embodiment, the lithium source includes at least one of lithium hydroxide and lithium carbonate.

[0052] In one embodiment, the niobium source includes at least one of Nb-containing oxoacid salts, hydroxides, and oxides, such as niobium pentoxide (Nb₂O₅).

[0053] In one embodiment, the antimony source includes at least one of Sb-containing oxyacid salts, hydroxides, and oxides, such as antimony trioxide (Sb₂O₃) or antimony pentoxide (Sb₂O₅).

[0054] In one embodiment, the sulfur content of the nickel hydroxide is ≤800 ppm, the particle size D50 is 10–12 μm, the δPSD is 1.15–1.25, where δPSD is the span of particle size measured by volumetric particle size distribution of the nickel hydroxide, δPSD = (d90-d10) / d50, and the specific surface area is 20–24 m². 2 / g; tap density is 1.8–2.5 g / cm³. 3 Magnetic foreign matter MI < 30 ppb; Moisture content of nickel hydroxide < 3000 ppm.

[0055] In one embodiment, the molar ratio of the nickel hydroxide and the lithium source, based on the elements of nickel and lithium, is 1:(1.03 to 1.05), for example, 1:1.04.

[0056] In one embodiment, the mass of the niobium source is 0.1% to 0.3% of the mass of the nickel hydroxide, for example, 0.1%, 0.12%, 0.15%, 0.18%, 0.2%, 0.22%, 0.25%, 0.28%, 0.3%, etc.

[0057] In one embodiment, the antimony source is 0.1% to 0.3% of the mass of the nickel hydroxide, for example, 0.1%, 0.12%, 0.15%, 0.18%, 0.2%, 0.22%, 0.25%, 0.28%, 0.3%, etc.

[0058] This invention ensures that the cathode material has better electrochemical performance and structural stability by using appropriate proportions of nickel hydroxide, lithium source, niobium source and antimony source.

[0059] In one embodiment, the mixing speed is 900–1100 rpm, such as 900 rpm, 950 rpm, 980 rpm, 1000 rpm, 1020 rpm, 1050 rpm, 1080 rpm, 1100 rpm, etc., and the mixing time is 30–50 min, such as 30 min, 35 min, 40 min, 45 min, 50 min, etc. This invention, through appropriate mixing speed and time, ensures thorough mixing of the materials, laying a solid foundation for obtaining excellent electrochemical cathode materials.

[0060] In one embodiment, the sintering temperature is 600–800°C, such as 600°C, 630°C, 650°C, 670°C, 700°C, 720°C, 750°C, 780°C, 790°C, 800°C, etc., and the sintering time is 10–16 hours, such as 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, or 16 hours. This invention employs appropriate sintering treatment and timing to ensure the crystallinity of the cathode material, giving it a specific microstructure, allowing primary particles to grow to a suitable particle size range, and enabling the cathode material to have suitable tap density and specific surface area, thereby ensuring excellent electrochemical performance of the cathode material.

[0061] In one embodiment, the oxygen-containing atmosphere contains 98% to 99.5% oxygen by volume, for example, 98%, 98.5%, 99%, 99.5%, etc. In the oxygen-containing atmosphere of the present invention, the oxygen is present at the aforementioned suitable volume percentage, thereby ensuring that the cathode material has a specific microstructure and better electrochemical performance.

[0062] In one embodiment, the heating rate of the sintering process is 2–4 °C / min, for example, 2 °C / min, 2.5 °C / min, 3 °C / min, 3.5 °C / min, or 4 °C / min. In the sintering process of the present invention, the material is heated to 600–800 °C at the above-mentioned heating rate and held at 600–800 °C for 10–16 hours.

[0063] In one embodiment, after the sintering process, the material is cooled in the furnace to room temperature, and then crushed and screened.

[0064] In a preferred embodiment, a method for preparing a cobalt-free cathode material includes the following steps:

[0065] (a) Mix nickel hydroxide and LiOH at a transition metal Ni:Li molar ratio of 1:(1.03 to 1.05), then add 0.1% to 0.3% of niobium oxide and 0.1% to 0.3% of antimony oxide by weight of nickel hydroxide, and perform dry mixing in a mixer at a speed of 900 to 1100 rpm for 30 to 50 minutes. After thorough mixing, a mixture is obtained.

[0066] (b) The mixture from step (a) is transferred to an atmosphere furnace and subjected to high-temperature sintering in a sintering atmosphere. The temperature is increased to 600-800°C at a heating rate of 2-4°C / min and calcined for 10-16 hours. The volume percentage of oxygen in the sintering atmosphere is 98%-99.5%. The mixture is cooled in the furnace and the resulting material is subjected to non-grading crushing and 325-mesh sieving to obtain cobalt-free lithium nickel oxide cathode material.

[0067] According to another aspect of the present invention, the present invention also relates to a positive electrode sheet, comprising the cobalt-free positive electrode material described above or the cobalt-free positive electrode material prepared by the method for preparing the cobalt-free positive electrode material described above.

[0068] In one embodiment, the positive electrode sheet of the present invention includes a positive electrode current collector and a positive electrode material layer disposed on at least one side surface of the positive electrode current collector. The positive electrode material layer contains the aforementioned cobalt-free positive electrode material, and further includes a conductive agent and a binder. In one embodiment, a positive electrode slurry is formed by mixing the cobalt-free positive electrode material, the conductive agent, the binder, and a solvent. The positive electrode slurry is then coated onto at least one side surface of the positive electrode current collector, followed by drying and rolling to obtain the positive electrode sheet.

[0069] According to another aspect of the present invention, the present invention also relates to a battery, including the cobalt-free cathode material described above or the cobalt-free cathode material prepared by the method for preparing the cobalt-free cathode material described above.

[0070] The present invention contains a battery with high capacity and high initial efficiency containing the above-mentioned cobalt-free cathode material.

[0071] In one embodiment, the battery of the present invention includes a positive electrode, a negative electrode, a separator, and an electrolyte.

[0072] According to another aspect of the invention, the invention also relates to an electrical device including the aforementioned battery. The electrical device may include a digital camera, a mobile phone, a power bank, etc.

[0073] The following explanation, in conjunction with specific embodiments, comparative examples, and accompanying drawings, further clarifies the situation.

[0074] The nickel hydroxides involved in the various embodiments and comparative examples of this invention are from Huayou Company, NQ01C2306049.

[0075] Example 1

[0076] A method for preparing a cobalt-free cathode material includes the following steps:

[0077] (1) Mix nickel hydroxide and LiOH according to the transition metal Ni:Li molar ratio of 1:1.04, then add 0.2% of niobium pentoxide and 0.2% of antimony trioxide by weight of nickel hydroxide, and dry mix in a mixer at a speed of 1000 rpm for 40 min. After thorough mixing, a mixture is obtained.

[0078] (2) The mixture in step (1) is transferred to an atmosphere furnace and sintered at high temperature in a sintering atmosphere. The temperature is increased to 700℃ for 15h at a heating rate of 2.5℃ / min. The volume percentage of oxygen in the sintering atmosphere is 99%. The mixture is cooled with the furnace. The resulting material is then subjected to non-grading crushing and 325-mesh sieve treatment to obtain cobalt-free lithium nickel oxide cathode material.

[0079] The charge / discharge capacity diagram of the battery corresponding to the cobalt-free cathode material in this embodiment can be found in [reference needed]. Figure 1 .

[0080] Example 2

[0081] A method for preparing a cobalt-free cathode material includes the following steps:

[0082] (1) Mix nickel hydroxide and LiOH according to the transition metal Ni:Li molar ratio of 1:1.04, then add 0.1% of niobium pentoxide and 0.2% of antimony trioxide by weight of nickel hydroxide, and dry mix in a mixer at a speed of 1000 rpm for 40 min. After thorough mixing, a mixture is obtained.

[0083] (2) The mixture in step (1) is transferred to an atmosphere furnace and sintered at high temperature in a sintering atmosphere. The temperature is increased to 725°C for 15 hours at a heating rate of 2.5°C / min. The volume percentage of oxygen in the sintering atmosphere is 99%. The mixture is cooled with the furnace. The resulting material is then subjected to non-grading crushing and 325-mesh sieve treatment to obtain cobalt-free lithium nickel oxide cathode material.

[0084] The X-ray diffraction pattern of the cobalt-free cathode material in this embodiment is as follows: Figure 2 As shown.

[0085] Example 3

[0086] A method for preparing a cobalt-free cathode material includes the following steps:

[0087] (1) Mix nickel hydroxide and LiOH according to the transition metal Ni:Li molar ratio of 1:1.04, then add 0.3% of niobium pentoxide and 0.2% of antimony trioxide by weight of nickel hydroxide, and dry mix in a mixer at a speed of 1000 rpm for 40 min. After thorough mixing, a mixture is obtained.

[0088] (2) The mixture obtained in step (1) is transferred to an atmosphere furnace and subjected to high-temperature sintering in a sintering atmosphere. The temperature is increased to 700°C at a heating rate of 2.5°C / min and calcined for 15 hours. The volume fraction of oxygen in the sintering atmosphere is 99%. The mixture is cooled with the furnace. The resulting material is then subjected to non-grading crushing and 325-mesh sieve treatment to obtain cobalt-free lithium nickel oxide cathode material.

[0089] The scanning electron microscope image of the cobalt-free cathode material in this embodiment is shown below. Figure 3 As shown.

[0090] Example 4

[0091] A method for preparing a cobalt-free cathode material includes the following steps:

[0092] (1) Mix nickel hydroxide and LiOH according to the transition metal Ni:Li molar ratio of 1:1.03, then add 0.2% of niobium pentoxide and 0.1% of antimony trioxide by weight of nickel hydroxide, and dry mix in a mixer at a speed of 1000 rpm for 40 min. After thorough mixing, a mixture is obtained.

[0093] (2) The mixture obtained in step (1) is transferred to an atmosphere furnace and subjected to high-temperature sintering in a sintering atmosphere. The temperature is increased to 700°C at a heating rate of 2.5°C / min and calcined for 15 hours. The volume fraction of oxygen in the sintering atmosphere is 99%. The mixture is cooled with the furnace. The resulting material is then subjected to non-grading crushing and 325-mesh sieve treatment to obtain cobalt-free lithium nickel oxide cathode material.

[0094] Example 5

[0095] A method for preparing a cobalt-free cathode material includes the following steps:

[0096] (1) Mix nickel hydroxide and LiOH according to the transition metal Ni:Li molar ratio of 1:1.04, then add 0.2% of niobium pentoxide and 0.3% of antimony trioxide by weight of nickel hydroxide, and dry mix in a mixer at a speed of 900 rpm for 40 min. After thorough mixing, a mixture is obtained.

[0097] (2) The mixture obtained in step (1) is transferred to an atmosphere furnace and subjected to high-temperature sintering in a sintering atmosphere. The temperature is increased to 700°C at a heating rate of 2.5°C / min and calcined for 15 hours. The volume fraction of oxygen in the sintering atmosphere is 99%. The mixture is cooled with the furnace. The resulting material is then subjected to non-grading crushing and 325-mesh sieve treatment to obtain cobalt-free lithium nickel oxide cathode material.

[0098] Example 6

[0099] A method for preparing a cobalt-free cathode material includes the following steps:

[0100] (1) Mix nickel hydroxide and LiOH according to the transition metal Ni:Li molar ratio of 1:1.04, then add 0.2% of niobium pentoxide and 0.2% of antimony trioxide by weight of nickel hydroxide, and dry mix in a mixer at a speed of 900 rpm for 50 min. After thorough mixing, a mixture is obtained.

[0101] (2) The mixture in step (1) is transferred to an atmosphere furnace and sintered at high temperature in a sintering atmosphere. The temperature is increased to 800°C at a heating rate of 3°C / min and calcined for 10 hours. The volume percentage of oxygen in the sintering atmosphere is 99.5%. The mixture is cooled with the furnace. The resulting material is then subjected to non-grading crushing and 325-mesh sieve treatment to obtain cobalt-free lithium nickel oxide cathode material.

[0102] Example 7

[0103] A method for preparing a cobalt-free cathode material includes the following steps:

[0104] (1) Mix nickel hydroxide and LiOH according to the transition metal Ni:Li molar ratio of 1:1.04, then add 0.2% of niobium pentoxide and 0.2% of antimony trioxide by weight of nickel hydroxide, and dry mix in a mixer at a speed of 1100 rpm for 30 min. After thorough mixing, a mixture is obtained.

[0105] (2) The mixture in step (1) is transferred to an atmosphere furnace and subjected to high-temperature sintering in a sintering atmosphere. The temperature is increased to 600°C at a heating rate of 2°C / min and calcined for 16 hours. The volume percentage of oxygen in the sintering atmosphere is 98%. The mixture is cooled with the furnace. The resulting material is then subjected to non-grading crushing and 325-mesh sieve treatment to obtain cobalt-free lithium nickel oxide cathode material.

[0106] Example 8

[0107] A method for preparing a cobalt-free cathode material, wherein the sintering temperature is 850°C, and other conditions are the same as in Example 1.

[0108] Comparative Example 1

[0109] A method for preparing a cobalt-free cathode material includes the following steps:

[0110] (1) Mix nickel hydroxide and LiOH according to the transition metal Ni:Li molar ratio of 1:1.04, then add 0.2% of the amount of niobium pentoxide in nickel hydroxide, and dry mix in a mixer at a speed of 1000 rpm for 40 min. After thorough mixing, a mixture is obtained.

[0111] (2) The mixture obtained in step (1) is transferred to an atmosphere furnace and subjected to high-temperature sintering in a sintering atmosphere. The temperature is increased to 700℃ at a heating rate of 2.5℃ / min and calcined for 15h. The volume fraction of oxygen in the sintering atmosphere is 99%. The mixture is cooled with the furnace. The resulting material is subjected to non-grading crushing and 325-mesh sieve treatment to obtain cobalt-free cathode material.

[0112] The scanning electron microscope image of the cathode material in this comparative example is shown below. Figure 4 As shown.

[0113] Comparative Example 2

[0114] A method for preparing a cobalt-free cathode material includes the following steps:

[0115] (1) Mix nickel hydroxide and LiOH according to the transition metal Ni:Li molar ratio of 1:1.04, then add 0.2% of antimony trioxide by weight of nickel hydroxide, and dry mix in a mixer at a speed of 1000 rpm for 40 min. After thorough mixing, a mixture is obtained.

[0116] (2) The mixture obtained in step (1) is transferred to an atmosphere furnace and subjected to high-temperature sintering in a sintering atmosphere. The temperature is increased to 700℃ at a heating rate of 2.5℃ / min and calcined for 15h. The volume fraction of oxygen in the sintering atmosphere is 99%. The mixture is cooled with the furnace. The resulting material is subjected to non-grading crushing and 325-mesh sieve treatment to obtain cobalt-free cathode material.

[0117] Experimental Example

[0118] 1. The specific surface area, residual alkali content, XRD, and tap density of the cathode materials in the examples and comparative examples were tested respectively. The test methods are as follows:

[0119] 1. Tap density test method

[0120] Pour the weighed sample into a clean test tube, insert the test tube into the support of the vibratory compactor, vibrate at an amplitude of 3 mm for 3000 cycles or 12 minutes, and record the volume as the compacted volume V. The compacted density of the powder is calculated using the formula ρ = m / V, where ρ is the compacted density of the powder, in g / cm³. 3 m is the mass of the powder in grams; V is the tapped volume of the powder in centimeters. 3 .

[0121] 2. Residual Alkali Test Method

[0122] The prepared high-nickel ternary cathode material and deionized water were mixed at a mass ratio of 5:100 and stirred at a speed of 200 rpm to 400 rpm for 5 min. After filtration by a vacuum pump, the mixture was titrated with 0.1 M hydrochloric acid solution at equivalence points to determine the content of residual LiOH and residual Li2CO3 on the surface of the high-nickel ternary cathode material.

[0123] 3. Specific surface area testing method

[0124] Measured using a surface area analyzer according to GB / T19587-2017.

[0125] 4. XRD Testing Methods

[0126] The RIGAL Smartlab XRD diffractometer was used with a Cu target as the radiation source. The scanning range was 10°–80°, the scanning speed was 1° / min, and the step size was 0.05°.

[0127] The test results are shown in Table 1.

[0128] Table 1. Test results of specific surface area, residual alkali content, full width at half maximum (FWHM(003)), and tap density.

[0129]

[0130] II. Battery Performance Testing

[0131] The cathode materials prepared in each embodiment and comparative example are further used to prepare batteries. The battery preparation method specifically includes:

[0132] The positive electrode material, acetylene black, and polyvinylidene fluoride were mixed in a mass ratio of 90:5:5, with an appropriate amount of N-methylpyrrolidone added as a dispersant. The mixture was then ground into a slurry, which was uniformly coated onto aluminum foil and vacuum dried at 120°C for 12 hours. The dried electrode was then rolled using a roller press, and the aluminum foil was cut into circular electrode sheets with a diameter of 1.3 cm using a slicing machine. The loading of the active material was controlled at 12 g / cm³. 2Afterwards, half-cells were assembled in an argon atmosphere glove box, with the water pressure controlled to be ≤0.1 pm and the oxygen partial pressure controlled to be ≤0.1 pm. Lithium metal was used as the negative electrode, 1M LiPF6 solution was used as the electrolyte, and the solvents were FEC, DEC and DMC in a volume ratio of 1:1:1. The assembled cells were CR2032 type coin cells.

[0133] Test parameters: constant current charge and discharge, voltage range of 2.5-4.3V, current density of 0.33C.

[0134] The performance test results of the batteries corresponding to each embodiment and comparative example are shown in Table 2.

[0135] Table 2 Battery performance test results

[0136]

[0137] The cobalt-free cathode material obtained by the method of the present invention can fix surface oxygen, reduce metal dissolution, and improve the reversibility of material phase transition. As shown in Table 2, the batteries prepared in each embodiment have higher charge-discharge capacity and first-time efficiency. Comparative Example 1 only added niobium oxide, and Comparative Example 2 only added antimony oxide, which could not exert a synergistic effect. The batteries prepared with the cathode materials obtained had low charge-discharge capacity and low first-time efficiency.

[0138] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A cobalt-free cathode material, characterized in that, The chemical formula of the cobalt-free cathode material includes Li x Ni 1-q- m Nb q Sb m O2, wherein 1.03≤x≤1.05, 0.001≤q≤0.003, 0.001≤m≤0.003; the surface of the cobalt-free cathode material has a nanoscale cation mixed phase layer; the surface of the cobalt-free cathode material has Nb-O ionic bonds; the thickness of the nanoscale cation mixed phase layer is 5~10nm; the full width at half maximum (FWHM(003)) of the cobalt-free cathode material is 0.09°~0.12°; the residual alkali content of the cobalt-free cathode material is 3000~5000ppm; the specific surface area of ​​the cobalt-free cathode material is 0.2~0.4m². 2 / g; the tap density of the cobalt-free cathode material is 2.2~3 g / cm³. 3 .

2. The method for preparing the cobalt-free cathode material as described in claim 1, characterized in that, Includes the following steps: Nickel hydroxide, lithium source, niobium source, and antimony source are mixed and then sintered in an oxygen-containing atmosphere. The lithium source includes at least one of lithium hydroxide and lithium carbonate. The niobium source includes at least one of Nb-containing oxyacid salts, hydroxides, and oxides. The antimony source includes at least one of Sb-containing oxyacid salts, hydroxides, and oxides. The molar ratio of nickel hydroxide to lithium source, based on nickel and lithium elements, is 1:(1.03~1.05). The mass of the niobium source is 0.1%~0.3% of the mass of the nickel hydroxide. The mass of the antimony source is 0.1%~0.3% of the mass of the nickel hydroxide. The sulfur content of the nickel hydroxide is ≤800ppm, and the particle size D50 is 10~12μm. δPSD = 1.15~1.25; specific surface area is 20~24 m² 2 / g; tap density is 1.8~2.5g / cm³ 3 Magnetic foreign matter <30ppb; Moisture content of nickel hydroxide <3000ppm.

3. The method for preparing the cobalt-free cathode material according to claim 2, characterized in that, The mixing speed is 900~1100 rpm, and the mixing time is 30~50 min.

4. The method for preparing the cobalt-free cathode material according to claim 2, characterized in that, It includes at least one of the following features (1) to (3): (1) The sintering temperature is 600~800℃ and the sintering time is 10~16h; (2) In the oxygen-containing atmosphere, the volume percentage of oxygen is 98%~99.5%; (3) The heating rate of the sintering treatment is 2~4℃ / min.

5. The method for preparing the cobalt-free cathode material according to claim 2, characterized in that, After the sintering process, the material is cooled in the furnace, and then crushed and screened.

6. A battery, characterized in that, The cobalt-free cathode material includes the cobalt-free cathode material according to claim 1 or the cobalt-free cathode material prepared by any one of claims 2 to 5.

7. An electrical appliance, characterized in that, Includes the battery as described in claim 6.

Citation Information

Patent Citations

  • Layered oxide material and preparation method thereof, positive electrode material, positive electrode plate and lithium ion battery

    CN115974177A